GAP Activites to Improve Islamic English Speaking Skill: Classroom Action Research - Oktavia, Yeki (GHAITSA : Islamic Education Journal, 2023)
The purpose of this study was to determine whether there was a significant effect of the use of information gap techniques on improving the speaking ability of seventh grade students of SMP Negeri 6 Bengkulu City. The method used in this research is classroom action research. The sample of this study was 28 students of class VII SMP Negeri 6 Bengkulu City. The instrument used in this study was documentation and a test about students' speaking ability which was declared valid. Data analysis technique, the researcher used SPSS version 16.0 to determine the mean between pre-test and post-test. Data analysis techniques are Normality Test and Paired T-Test. Based on the results of data calculations, after learning to speak English using the information gap technique on students' speaking skills, it can be concluded that the Paired Samples t-Test was used because the data of English Speaking Skill (Pretest) and English Speaking Skill (Posttest) were normally distributed. It can be seen that the value of the Paired Samples t-Test (t-count) is 10.380 and the t-table is 2.056 with a p-value of 0.000. Because the value of t-count > t-table or p value <0.05, it is said that there is an average difference between English Speaking Skill (Pretest) and English Speaking Skill (Posttest). This means that the information gap activity method is significant to improve the speaking skills of class VII student of SMP N 6 Bengkulu city in the 2021/2022 academic year.